ESG, Nilai Perusahaan dan Kinerja: Peran Moderasi Audit Internal dan Eksternal - Maulinda Safitri; Tito IM. Rahman Hakim; Rahmat Zuhdi; Anis Wulandari (Owner : Riset dan Jurnal Akuntansi, 2026)
The current study investigates the dynamics among Environmental, Social, and Governance (ESG) disclosure, value and performance of the firm, incorporating audit quality and audit committee as moderating factors. Panel data regression is utilized to analyze 455 observations from non-financial firms listed on the Indonesia Stock Exchange over the 2017–2023 period. The sample is filtered through purposive sampling based on some predetermined criteria. The results exhibit (1) ESG disclosure failed to significantly affect firm value but negatively affect performance; (2) for moderation analysis only the interaction between ESG disclosure and audit quality is significant, while the rest is not significant. These findings advance the theoretical understanding of the role of audit mechanisms in ESG contexts in Indonesia.  This study's findings also offer valuable insights for several stakeholders. Companies can leverage them to enhance the effectiveness of their ESG reporting assurance mechanisms. Investors gain awareness of the limitations in current internal assurance practices that affect the credibility of ESG disclosures. For policymakers, the results highlight the importance of refining audit functions within the ESG reporting framework through regulatory measures to better support corporate value creation.